Antimicrobial Effects of Mastic Extract Against Oral and Periodontal Pathogens. Issue 5 (1st May 2017) - Koychev, Stefka; Dommisch, Henrik; Chen, Hong; Pischon, Nicole
Abstract : Background: Various antimicrobial agents are widely used in the therapy of oral inflammatory diseases. However, their side effects and the appearance of drug resistance justify research on natural antimicrobial agents to target oral pathogens that are safe for the host. In the present study, antimicrobial properties of mastic extract on commensal and pathogenic oral bacteria, as well as its possible cytotoxic effect toward cells of epithelial and mesenchymal origin, were evaluated and compared with the common antimicrobial agents hydrogen peroxide (H2 O2 ) and chlorhexidine digluconate (CHX). Methods: Oral and periodontal pathogens ( Porphyromonas gingivalis, Streptococcus mutans [Sm], Streptococcus oralis, Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum, Prevotella intermedia, and Prevotella nigrescens ) were treated with different concentrations of mastic extract, 3% H2 O2, and 0.2% CHX, and evaluated with an agar diffusion test. The cytotoxic effect of mastic extract was tested on four cell lines of epithelial and mesenchymal origin (HaCaT, SaOS‐2, MC3T3‐E1, periodontal ligament [PDL] cells) by neutral red and 2, 3‐bis‐(2‐methoxy‐4‐nitro‐5‐sulfophenyl)‐2H‐tetrazolium‐5‐carboxanilide assay. Results: Mastic extract led to significantly ( P ≤0.016) increased inhibition of the tested periodontal pathogens compared with H2 O2 . No effect of mastic extract was observed on Sm . Mastic extract showed beneficial effects on cell viability because viability values of tested cells were significantly ( P ≤0.016) lower for cells treated with CHX and H2 O2 compared with mastic extract–treated cells after stimulation for 2, 4, and 6 hours. Conclusion: The present data demonstrate mastic extract's inhibition of periodontal pathogens, as well as beneficial effects on cell viability, compared with H2 О2, suggesting that it could be considered an alternative antibacterial agent in the prevention of periodontal disease.